COMPARED EFFECTIVENESS, SAFETY AND COST OF DEXMEDETOMIDINE WITH MIDAZOLAM: A REVIEW - Rahayu, Nila Rusdi; Mutripah, Siti (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
Dexmedetomidine, an alpha 2 receptor agonist sedative drug, has recently garnered attention as a viable alternative to midazolam, a widely used benzodiazepine for sedation in adult patients. The aim of this study was to conduct a comprehensive comparison of the clinical sedative efficacy, cost-effectiveness, and safety profiles of dexmedetomidine versus midazolam, utilizing a randomized controlled trial design. The search encompassed several databases, including PubMed, Scopus, Web of Knowledge, CINAHL, the United States National Library of Medicine, and Google Scholar for Systematic Reviews, using the keywords 'dexmedetomidine,' 'midazolam,' and 'effectiveness.' The findings revealed that dexmedetomidine demonstrated a more favorable safety profile, with a lower incidence of delirium compared to midazolam. In terms of effectiveness, no significant differences were observed between the two drugs for local sedation. Notably, adult patients treated with dexmedetomidine had a shorter Intensive Care Unit (ICU) stay (7 days) compared to those receiving midazolam (10 days). Similarly, pediatric ICU treatment indicated a shorter duration with dexmedetomidine (20 hours) as opposed to midazolam (38 hours). Regarding cost-effectiveness, dexmedetomidine emerged as a cost-saving option, being approximately 10% cheaper than midazolam for adult ICU patients. These findings collectively highlight the advantages of dexmedetomidine over midazolam, encompassing superior safety, effectiveness, and cost-efficiency, thus providing valuable insights for healthcare practitioners and decision-makers.